HIGHER ECOLOGICAL EDUCATION OF UKRAINE: HISTORY OF FORMATION AND CURRENT STATE - Safranov, Tamerlan (Educological discourse, 2021)
The environmental component of education determines the socio-economic foundations of society and is the basic component of the state environmental policy. The nature of interaction with the environment at the personal level and society makes it possible to implement the concept of sustainable development, and therefore the assessment of the current state of higher environmental education in Ukraine is an urgent problem. The purpose of article is to analyze the formation and current state of higher environmental education in Ukraine, which is the central link in the system of continuous environmental education. An important step in the development of the system of continuous environmental education, in particular higher environmental education, was the development of the Concept of Environmental Education of Ukraine (2001), the principles of which were not properly implemented. The content of higher environmental education is reflected in four generations of standards for higher environmental education in Ukraine, which took into account changes in the relevant regulatory and legislative documents and requirements for the content and results of educational activities of higher educational institutions within certain areas of training and specialties. The article describes the structure and content of standards of higher environmental education in Ukraine. Despite the fact that the environmental component currently prevails in the form of education that most consider education for sustainable development, yet this is only the beginning of the formation of a new system-integrated model of education for sustainable development. The importance of greening and ideas of sustainable development is reflected in the current standards of higher education in Ukraine for applicants for higher education "bachelor" of all specialties. But the environmental component is still absent in the educational programs and curricula of many specialties of "non-environmental" higher education institutions, is not due attention is paid to the greening of higher education in Ukraine. Some provisions of the existing Concept of Environmental Education of Ukraine are no longer relevant, which leads to the development of a modern Concept, and, perhaps, a separate Concept of higher environmental education in Ukraine. In recent years, there has been a decline in state interest in the training of environmentalists, so it is advisable to develop measures to improve the training of applicants for higher environmental education.